Study of the climate change impact on fishers’ livelihood near the Padma river in Munshiganj, Bangladesh - Ema, Noore Safa; Hossain, Md Saddam; Uddin, Md Nagim; Rahman, Mohammad Matiur; Hossain, Zakir (Asian Journal of Medical and Biological Research, 2021)
Climate change is a contemporary global threat to the whole world especially in the coastal area like Bangladesh. Bangladesh is extremely vulnerable to climate change impacts because of its geographical location. This research is an attempt to assess the impacts of climate change on fishersʹ livelihood of a selected climate hotspot zone Munshiganj. In the study area, the average sex ratios of male and female were 56.67% and 43.33%, respectively and their religion ratio were Islam 45% and Hindu 55%. There was 60% nuclear family and 40% joint family. About 86.4% house was tin-shed and drinking water source was only tube well. In Munshiganj, 11% fishers were illiterate, 27% had primary, 38% had secondary, 16% had higher secondary and 8% had bachelor. Most of the people about 59% were depended on Upazila Health Complex for their health issues. Highest percentage of fishers about 40% had an annual income of 20,001 to 24,000 BDT. About 62.7% fishers were agreed with the statements: reduce fish production, damage fishing ground, blockage of fish migration road, damage biodiversity, increasing temperature, enhance soil erosion, reduce rainfall, siltation, water flow, storm frequency, changing spawning season, decrease fish production, extinction fish species. In study area, women and children are affected severely i.e. malnutrition, education, treatment, early marriage etc. The present study clearly indicates that there are visible changes in livelihood condition of fishers‟ in the study areas of Munshiganj. Asian J. Med. Biol. Res. December 2020, 6(4): 777-784